Purpose, Process and Future Direction of Disability Research - Symeonidou, Simoni.; Beauchamp-Pryor, Karen. (Studies in Inclusive Education, 2013)
Purpose, Process and Future Direction of Disability Research brings together the collective experience of an international network of early career researchers who set out to discuss the complexity of researching disability. As newcomers to the research process, the researchers detail their apprehensions about embarking on doctoral research, together with the struggles they experienced along the way, and importantly the motivation that drove them to complete their projects. Contributors present an open and honest reflection on their research experience. Interests, motives and values which underpinned the direction of their research projects are explored, questioning whether their beliefs were subsequently challenged, changed or validated. Research decisions were driven by a range and combination of personal experience of disability and professional experience of working with disabled people. The influence of personal and professional approaches within research is addressed, along with subsequent dilemmas. Ideological battles are detailed, which include: the place of the social model of disability in research; and the oppressive nature of doing disability research. The researchers identify and examine their experience throughout the process of analysis, writing-up and presenting data and question how far their data resulted in confusions or conclusions. Contributors explore their moral and political position as researchers, and the potential influence on the validity of their findings. Issues about dissemination and the impact of their findings are also considered. Future research aims and challenges are identified with each contributor critically questioning the unfinished business that their research has involved. Essential reading recommended for students and supervisors engaged in disability studies and inclusive education.